Entrepreneurial Behaviour of Anthurium Growers in Aizawl District of Mizoram State - J.H. Gaikwad and V. Lalhriatpuii, (Indian Journal of Extension Education, 2018)
The study was conducted with 120 anthurium growers in Aizawl district of Mizoram state. The study revealed thatmajority of the anthurium growers under the study were of middle age, mostly got middle school, high school and highersecondary school level of education, most of the farmers possess medium size of landholding and medium size of landarea under poly-house. Majority of them had medium level of annual income, medium marketing behaviour, mediumextension contact and medium mass media exposure. Majority of the respondents had medium level of entrepreneurialbehaviour followed by high and low level of entrepreneurial behaviour.